2002
DOI: 10.1200/jco.2002.09.034
|View full text |Cite|
|
Sign up to set email alerts
|

Temozolomide Plus Thalidomide in Patients With Advanced Melanoma: Results of a Dose-Finding Trial

Abstract: The combination of temozolomide and thalidomide was well tolerated and had antitumor activity in patients with advanced melanoma, including elderly patients over 70 years old.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 14 publications
1
32
0
1
Order By: Relevance
“…Eleven of the trials were published as full reports [8,10,12,13,15,16,19,20,24,26,28], while 10 were available only in abstract form [9, 11, 14, 17, 18, 21-23, 25, 27]. Patient characteristics and trial descriptions for those trials are shown in Table 2.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven of the trials were published as full reports [8,10,12,13,15,16,19,20,24,26,28], while 10 were available only in abstract form [9, 11, 14, 17, 18, 21-23, 25, 27]. Patient characteristics and trial descriptions for those trials are shown in Table 2.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…In addition, phase I or II trials investigating singleagent temozolomide (n ϭ 9) [8 -16], temozolomide plus IFN-␣ (n ϭ 6) [17][18][19][20][21][22], and temozolomide plus thalidomide (n ϭ 6) [23][24][25][26][27][28] were reviewed. Eleven of the trials were published as full reports [8,10,12,13,15,16,19,20,24,26,28], while 10 were available only in abstract form [9, 11, 14, 17, 18, 21-23, 25, 27].…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hwu et al studied thalidomide in combination with temozolomide in patients with unresectable stage III or stage IV melanoma without brain metastases [58]. TMZ 75 mg/m2/day for 6 weeks was followed by a 2-week break, and thalidomide at 200-400 mg/day.…”
Section: Role In Solid Tumorsmentioning
confidence: 99%
“…The humanized monoclonal antibody Vitaxin, which is directed against the a v b 3 integrin (Posey et al, 2001), and the angiogenesis inhibitor thalidomide, combined with the cytotoxic agent temozolomide (Hwu et al, 2002), are currently being tested in clinical trials for patients with metastatic melanoma. The combination of temozolomide and thalidomide was shown to be well tolerated and had antitumor activity in some patients with advanced melanoma (Hwu et al, 2002). A phase I trial of the angiogenesis inhibitor TNP-470, a derivative of fumagillin, resulted in the induction of long-term stable disease in one patient with progressive metastatic melanoma (Bhargava et al, 1999).…”
Section: Therapeutic Targeting Of Angiogenesis In Melanoma Patientsmentioning
confidence: 99%